NUTRITIONAL STATUS OF PEOPLE LIVING WITH HIV/ACQUIRED IMMUNODEFICIENCY SYNDROME - A CROSS-SECTIONAL STUDY - Hiremath, Ravishekar N; Patil, Shailaja S; Yadav, Arun K (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to assess the nutritional status of people living with HIV and acquired immunodeficiency syndrome (PLHAs) on antiretroviral treatment (ART) and their knowledge with respect to role of nutrition in maintaining their health and to know the association of various factors with nutritional status and knowledge among PLHAs attending ART centers. Methods: A cross-sectional study carried out at ART center of a tertiary care institution in Maharashtra. A total of 104 PLHAs who were started on ART for the 1st time and completed minimum 6 months of treatment and who gave consent were included in the study. Data were collected by personal interview technique after taking informed consent with the help of pre-tested, prevalidated questionnaire with predetermined scoring system along with anthropometric measurements and relevant investigations maintaining strict confidentiality. Those with <50% scores were marked as unsatisfactory and more than 50% as satisfactory. Data were entered into Excel Sheet and were analyzed with SPSS 17.1 software. Results: In our study, 51.92% of the study participants were female, mean age was 38.5±9.6, 14.42% were illiterate, 32% had undergone primary education, and equally had secondary education. 16.35% were drivers and almost all were married (96.15%). Mean hemoglobin (Hb%) before and after ART was 10.45±2.13 and 10.64±2.16, while mean CD4 count before and after ART was 177.26±146.52 and 413.69±266.25, respectively, while post-ART mean body mass index (BMI) was 20.55±3.07. Majority (75%) were on ART for more than 12 months. Majority (65.38%) had unsatisfactory score with respect to overall knowledge regarding nutrition. 28.85% were underweight and 2.88% obese; while 17.31% were overweight and rest were normal. 46.15% were anemic. Statistical significant difference was noted among age, educational status, marital status, knowledge score, and anemia status with respect to BMI. Logistic regression with BMI as an outcome showed that age binary had some association. It means that there are 2.7 times odds of normal BMI in higher age group. Statistically significant difference was also noted in mean CD4 count before and after ART therapy. Regression analysis showed that CD4 count post-ART depends on pre-ART CD4 count, ART duration, and gender of the individual. With each unit increases in pre-ART CD4 and ART duration, there is increase of 0.44 and 4.5 units in after ART CD4. Post-ART CD4 count increased more among females compared to males in our study. Conclusion: There exists a wide gap in PLHAs knowledge regarding nutritional aspects. The study also shows that good nutrition has good influence on CD4 count. PLHAs belonging to higher age 40 years, married, and educated, those who had better knowledge score and good Hb% had better nutrition. Therefore, there is an urgent need for nutritional interventions like frequent health educational sessions on nutrition to increase the knowledge of PLHAs can be emphasized during each follow-up visit at ART centers. There is a need to identify PLHAs with no or minimum nutritional support and provides nutritional supplementation, for which planning and policy section needs adequate research evidences from India.